Socio-Pedagogical Foundations of Improving the Environmental Education Readiness of Elementary School Students and Their Place in Education - Kuchkinov Abdumalik Yuldashovich; Mustarova Dildora Eshmamatovna (International Journal on Integrated Education, 2022)
This article discusses the environmental literacy of elementary school students and its place in society, focusing on the environment in elementary education. In addition, it provides areas where the acquisition of knowledge in this field is carried out.